A sociocognitive approach to business ethics: lessons from early industrializing Japan. Issue 3 (2nd July 2016) - von Staden, Peter
Abstract: Understanding transgression of business ethics in developed Western economies is different from that in developing economies where the institutional matrix that frames the market and transactions is in the process of fundamental change. This is particularly so when entrenched historical practices of close business and government interaction continue into the new era. In this environment the study of ethical forbearance may be more illuminating than transgression. Seen from a New Institutional Economics' perspective on the sociocognitive, our empirical study of Shibusawa Eiichi and Dan Takuma shows that ideology can play an important role in shaping ethical business practice.